Calvert, Katherine E. Modeling Motherhood in Weimar Germany: Political and Psychological Discourses in Women’s Writing. Camden House, 2023. - Andrea Schmidt (Studies in 20th & 21st Century Literature, 2026)
Review of Calvert, Katherine E. Modeling Motherhood in Weimar Germany: Political and Psychological Discourses in Women’s Writing. Camden House, 2023. pp. 178.
Keywords: motherhood; Weimar; feminism